Analisis Upaya Peningkatan Indeks Desa Membangun (IDM) di Negeri Porto, Kecamatan Saparua, Kabupaten Maluku Tengah - Nanlohy, Chelsy Feren; Nanlohy, Willem D.; Botanri, Adnan A. A. (HORIZON: Indonesian Journal of Multidisciplinary, 2025)
This study aims to analyze efforts to improve the Village Development Index (IDM) in Negeri Porto, Saparua District, Central Maluku Regency. The main focus of this study is to explore strategies that can be applied in the development of independent and sustainable villages. The method used in this study is qualitative, with data collection techniques through direct observation and interviews with the local community. The results of the study indicate that there is a significant correlation between the research objectives and the analytical methods used. This study also identifies several factors influencing the success of village development, including community participation and government policies. Additionally, this study is expected to contribute useful insights and information for the government in formulating long-term plans for village development, as well as assist the community in understanding the importance of environmental conservation and local economic development. Thus, this research not only focuses on theoretical aspects but also provides practical recommendations that can be implemented to improve the quality of life of rural communities. Further research is expected to expand the scope of the regions and cultures studied, so that the strategies developed can be more applicable and relevant in various contexts. This research is expected to serve as an evaluation tool for the government and communities in their efforts to achieve more equitable and sustainable development in Indonesia